Pengaruh Profitabilitas, Struktur Modal Dan Pertumbuhan Penjualan Terhadap Nilai Perusahaan Pada Perusahaan Sektor Consumer Goods Sub Sektor Cyclical Berbasis ESG Di Bursa Efek Indonesia Tahun 2020-2024 - Jessica; Lutfi Alhazami (Jurnal Riset Multidisiplin Edukasi, 2026)
This study investigates how earnings capacity, capital arrangement, and revenue expansion drive the overall market appraisal of a firm. Such a valuation serves as a critical benchmark, encapsulating investor sentiment regarding a company’s operational efficiency and future trajectory. Utilizing a quantitative framework backed by secondary data from the Indonesia Stock Exchange, the research employs multiple linear regression to test these variables, with Price to Book Value (PBV) serving as the primary proxy for corporate worth. The findings reveal that profitability exerts a significant positive influence on firm value, confirming that a company’s talent for generating net income is the foremost catalyst for bolstering investor confidence. Conversely, the debt-to-equity mix and sales growth do not appear to have a meaningful impact on market perception. These results suggest that market participants prioritize bottom-line results over financing strategies or top-line growth when assessing a firm’s quality. Consequently, the study implies that management must focus on sustainable profit optimization to strengthen corporate standing and enhance investment appeal within the capital market.